2010
DOI: 10.1177/0891241610379122
|View full text |Cite
|
Sign up to set email alerts
|

Food for Thought, Thought for Food: Consumption, Identity, and Ethnography

Abstract: Movements associated with lifestyle and consumption politics have gained increasing visibility in society and in sociological research, but scholars’ methodological insights for studying these issues have lagged behind. How might the lifestyles and consumption practices of researchers themselves shape data collection, and how might these movements affect researchers? The authors offer a collaborative, reflexive analysis of their experiences conducting fieldwork on three different consumption movements centered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Kerfoot thus conceptualized that his acceptance in this community was contingent upon his accepting what/who was offered as food, and that if he refused this, his learning would be constrained. Cherry, Ellis, and DeSoucey [33] write about how their consumptive identities (as a vegan researching animal rights activists, a near vegan researching cattle ranching, and a carnist researching politics of foie gras, respectively) also worked to shape what they could or could not learn from their participants. Their reflexive analysis reveals that access to their populations of interest entailed a process of negotiation in terms of their consumption practices and themselves, "…we needed to validate our identities by physically consuming certain items-or not-in front of our participants" (p. 236).…”
Section: Building Rapport Through Similaritymentioning
confidence: 99%
“…Kerfoot thus conceptualized that his acceptance in this community was contingent upon his accepting what/who was offered as food, and that if he refused this, his learning would be constrained. Cherry, Ellis, and DeSoucey [33] write about how their consumptive identities (as a vegan researching animal rights activists, a near vegan researching cattle ranching, and a carnist researching politics of foie gras, respectively) also worked to shape what they could or could not learn from their participants. Their reflexive analysis reveals that access to their populations of interest entailed a process of negotiation in terms of their consumption practices and themselves, "…we needed to validate our identities by physically consuming certain items-or not-in front of our participants" (p. 236).…”
Section: Building Rapport Through Similaritymentioning
confidence: 99%
“…Being both a researcher and a staff member at Yggdrasill illustrates the ethical dilemma of my ethnographic research (Cherry et al 2011;Jönsson 2012). I was there to gain information, as a researcher, but also to provide information, as a staff member.…”
Section: Creating Intimacy: Notes On Methodologymentioning
confidence: 99%
“…Furthermore, lifestyle is an expression of oneself and the accumulation of past experiences (Veal, 1993). Past studies also found that the consumption of food was influenced by each person's lifestyles, consumption practices and identities (Cherry et al, 2011).…”
Section: The Relationship Between Lifestyles and Destination Activitymentioning
confidence: 99%
“…Past studies have found that the consumption of food is influenced by each person's lifestyles, consumption practices and identities (Cherry, Ellis, & DeSoucey, 2011;Tellström et al, 2006). Food has extensive connotations; it not only fulfils our physiological needs but also provides intrinsic meanings connected to psychological, historical, social status, and symbolic aspects of our lives (Bell, 2000;Germann Molz, 2007;Kittler & Sucher, 2004).…”
Section: The Supply Demand and Underlying Meaning Of Foodmentioning
confidence: 99%
See 1 more Smart Citation